2011
DOI: 10.1152/ajpcell.00012.2011
|View full text |Cite
|
Sign up to set email alerts
|

Human myostatin negatively regulates human myoblast growth and differentiation

Abstract: Myostatin, a member of the transforming growth factor-␤ superfamily, has been implicated in the potent negative regulation of myogenesis in murine models. However, little is known about the mechanism(s) through which human myostatin negatively regulates human skeletal muscle growth. Using human primary myoblasts and recombinant human myostatin protein, we show here that myostatin blocks human myoblast proliferation by regulating cell cycle progression through targeted upregulation of p21. We further show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 33 publications
5
73
0
1
Order By: Relevance
“…The reduction in myostatin mRNA expression at 7 days with T treatment was accompanied by increases in myogenin mRNA expression in PD cells, which is supported recent literature highlighting myostatin's role for inhibiting myogenic differentiation [49,73,74]. Despite this, testosterone did not return absolute levels of myostatin expression to the low levels observed in the control cells.…”
Section: Discussionsupporting
confidence: 83%
“…The reduction in myostatin mRNA expression at 7 days with T treatment was accompanied by increases in myogenin mRNA expression in PD cells, which is supported recent literature highlighting myostatin's role for inhibiting myogenic differentiation [49,73,74]. Despite this, testosterone did not return absolute levels of myostatin expression to the low levels observed in the control cells.…”
Section: Discussionsupporting
confidence: 83%
“…Intriguingly, the cell-cycle regulator p21 and Myostatin (Mstn), both of which inhibit myoblast proliferation (4, 41-50), were significantly up-regulated in 4OH-Ttreated cells (Table S1). Myostatin is necessary for the balance between proliferation and differentiation of muscle progenitors embryonically and postnatally (41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Myostatin signaling activates expression of p21, inhibiting myoblast proliferation (41)(42)(43)(48)(49)(50)).…”
Section: Resultsmentioning
confidence: 99%
“…These data demonstrate that the increased expression of Mstn is responsible for the lack of proliferative expansion of Numb-deficient satellite cells. Mstn is an important regulator of postnatal myogenesis; it is expressed in quiescent satellite cells and inhibits their activation (41,43). It also inhibits myoblast proliferation, inducing differentiation (42,44,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the microenvironment and interactions with the myofiber may be important factors influencing fiber typespecific SC responses. Myostatin appears to be a key factor in regulating human SC function (34,37). We have recently demonstrated that elevated myostatin and elevated SC-specific myostatin levels in type II SCs may be one of the key factors impairing the myogenic capacity of muscle in older humans (37).…”
Section: Discussionmentioning
confidence: 99%